River Water Level Prediction Using Passive Microwave Signatures. A Case Study: The Bermejo Basin - Vittucci, Cristina (2014)
The aim of this work is to investigate the exploitation of radiometric acquisitions from satellite sensors at different microwave frequencies in view of the prediction of river water level. A case study has been identiﬁed in the Bermejo basin, in northern Argentina. This river is seasonally affected by severe ﬂooding events in the lower part, mostly due to rains occurring in the upper basin, that produce sediment loadings ﬂushing down along the lower basin thus changing the watercourse. While the effectiveness of microwave radiometry at Ka band for ﬂood moni- toring is consolidated in the literature, this study also considers X and C bands (provided by the Advanced Microwave Scanning Radiometer (AMSR) series together with the higher frequency) and highlights the better sensitivity to soil conditions of L band data (made recently available, thanks to SMOS) over moderately and densely vegetated areas. This study conﬁrms, ﬁrst, the well-known capability of passive microwave remote sensing instruments to record brightness temperature variations due to rainfall and ﬂoods occurred near river edges under different seasonal conditions. For this purpose, a multifrequency comparative analysis is conducted. Second, it investigates whether these properties can be exploited for ﬂood forecasting: a model which directly links the daily satellite measurements to the river water level has been tested, considering 1- to 7-day forecast horizons. The results show that forecasting models can take advantage of the sensitivity of low frequencies to soil moisture conditions in order to predict ﬂood peaks, despite the instrument?s low resolutions.